Composición química y actividades biológicas del género Zanthoxylum: una revisión (2021)
Zanthoxylum is a genus of plants in the family Rutaceae with a wide variety of chemical compounds that have been used by people in folk medicine long ago and now, with advances in science it has been possible to identify and classify the wide variety of chemical compounds present in its leaves, its bark and even in its wood. Due to the range of useful substances present in the plant, humans have been able to cope with different diseases such as diarrhea, cold, cough, rheumatism, ulcers, among others and with scientific advances it has been possible to test their different biological activities such as antimicrobial, platelet antiaggregation, cytotoxic and antitumor; all this is thanks to compounds such as lignans, alkaloids, flavonoids, coumarins, terpenes, among others. With the realization of this work we seek to know all those advances and studies that have been carried out with respect to the plants of the genus and understand how varied the composition of them is and the great usefulness that they can offer to the human being.